Climate Knowledge Products Revamped in the Undergraduate Agriculture Curricula: Alternative option to ensure the dynamic nature of curricula in Ethiopia - Belay, Berhanu; Ambaw, Gebermedihin; Amha, Yosef; Demissie, Teferi Dejene; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Climate change education plays a vital role in addressing the climate crisis (Vaughter, 2016). By incorporating climate knowledge products into the curriculum, enhancing the capacity of staff to teach the subject, improving teaching infrastructure, and providing necessary financial support, educational institutions can contribute to nurturing a knowledgeable and future-oriented workforce. The curriculum can be updated through various methods, such as introducing new climate-related programs or refurbishing existing curricula with contemporary knowledge to ensure its relevance and adaptability. Revamping integrates climate knowledge products into the existing curricula by including up-to-date content as a chapter and subchapter. Revamping a quick-win approach to incorporate climate knowledge in the curricula. This approach enables a quick-win solution for integrating climate knowledge into the curriculum, ensuring that students are exposed to essential climate-related concepts and information. Ethiopian Public universities engaged in a series of consultations to adopt a revamping approach as the preferred strategy for updating their curricula. The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) initiative facilitated these consultations, including seeking expert advice and budgetary support. Following the consultations, a dedicated university committee was established to assess the current climate-related curricula, identify areas of improvement, and propose strategies to fill the identified gaps. After thorough analysis, the committee successfully identified gaps in the existing curricula and revamped them. They developed comprehensive recommendations to address these gaps. To ensure the acceptance and future implementation of the proposed changes, a workshop was organized wherein university representatives were presented with the revamped curricula and invited to provide validation and feedback. The workshop participants validated the proposed revamped curricula. The validated curricula in the workshop were channeled to Universities, and the universities approved the validated and updated curricula through their academic channels for implementation. Of the 24 universities that participated in the validation workshop, 18 revamped their curricula in 6-10 departments and 4-12 courses in the College of Agriculture Sciences. The number of climate-related courses across universities was variable. Hence, 112 courses from 95 departments in 18 universities have revamped Climate Knowledge Products (CKP) in their curriculum, 95 teaching staff members are teaching the course, and 4480 students will benefit from the revamped exercises. We are making a follow-up to integrate climate knowledge products in the remaining universities to benefit from the experience of revamping. The lesson in revamping to update the curricula in climate-related courses in agriculture could be taken to update other programs (e.g., Health, Engineering, etc.) with climate knowledge products. The revamping of the postgraduate program could be done by scanning the postgraduate program, filling the gaps, and orientation and demand the creation of teaching staff and university administration at each stage. The linkage and the partnership between AICCRA and Ethiopian public universities is an initiative that has changed from a Memorandum of understanding to a memorandum of action, which has galvanized our collaboration to plan other gap-filling projects and activities.